Penerapan Metode Dbscan untuk Identifikasi Kluster Gempa Bumi di Daerah Yogyakarta - Wahyu Ajitomo; Irfan Pratama (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Earthquakes are one of the natural disasters that frequently occur in Indonesia, including the Yogyakarta region. A profound understanding of earthquake patterns and characteristics in this area is crucial for risk mitigation efforts and disaster preparedness. Clustering methods, such as Density-Based Spatial Clustering of Applications with Noise (DBSCAN), can provide an effective approach to identifying earthquake clusters with high density in the Yogyakarta region. This research used the DBSCAN method to identify earthquake clusters with specific magnitude strengths in the Yogyakarta region. Earthquake distribution data from 2017 to 2022 was used as the research sample. The clustering process considered the epsilon parameter and the minimum number of samples within a cluster. The analysis results revealed the existence of earthquake clusters with high density concentrated in specific locations in the Yogyakarta region. These clusters reflect clear spatial patterns and indicate significant seismic activity in the area. The conclusion of this study confirms the presence of earthquake patterns and clusters that can be identified using the DBSCAN method. These clusters provide further insight into the distribution of earthquakes in the Yogyakarta region and can serve as a reference for earthquake risk mitigation in the future. The findings of this research offer valuable insights for stakeholders in decision-making and planning responsive actions to earthquakes in the Yogyakarta region.